An Individualized Low-Pneumoperitoneum-Pressure Strategy May Prevent a Reduction in Liver Perfusion during Colorectal Laparoscopic Surgery - Luis Enrique Olmedilla Arnal; Oscar Diaz Cambronero; Guido Mazzinari; José María Pérez Peña; Jaime Zorrilla Ortúzar; Marcos Rodríguez Martín; Maria Vila Montañes; Marcus J. Schultz; Lucas Rovira; Maria Pilar Argente Navarro; on behalf of the IPPColLapSe II investigators (Biomedicines, 2023)
High intra-abdominal pressure (IAP) during laparoscopic surgery is associated with reduced splanchnic blood flow. It is uncertain whether a low IAP prevents this reduction. We assessed the effect of an individualized low-pneumoperitoneum-pressure strategy on liver perfusion. This was a single-center substudy of the multicenter ‘Individualized Pneumoperitoneum Pressure in Colorectal Laparoscopic Surgery versus Standard Therapy II study’ (IPPCollapse–II), a randomized clinical trial in which patients received an individualized low-pneumoperitoneum strategy (IPP) or a standard pneumoperitoneum strategy (SPP). Liver perfusion was indirectly assessed by the indocyanine green plasma disappearance rate (ICG–PDR) and the secondary endpoint was ICG retention rate after 15 min (R15) using pulse spectrophotometry. Multivariable beta regression was used to assess the association between group assignment and ICG–PDR and ICG–R15. All 29 patients from the participating center were included. Median IAP was 8 (25th–75th percentile: 8–10) versus 12 (12,12) mmHg, in IPP and SPP patients, respectively (p < 0.001). ICG–PDR was higher (OR 1.42, 95%-CI 1.10–1.82; p = 0.006) and PDR–R15 was lower in IPP patients compared with SPP patients (OR 0.46, 95%-CI 0.29–0.73; p = 0.001). During laparoscopic colorectal surgery, an individualized low pneumoperitoneum may prevent a reduction in liver perfusion.